On the accuracy of RTTOV-SCATT for radiative transfer at all-sky microwave and submillimeter frequencies. (June 2022) - Barlakas, Vasileios; Galligani, Victoria Sol; Geer, Alan J.; Eriksson, Patrick
Highlights: RTTOV-SCATT is able to simulate scattering radiative transfer at submillimeter frequencies. RTTOV-SCATT errors are much smaller than the assigned observation error in data assimilation. δ -Eddington method shows weaknesses at high single scattering albedo and asymmetry parameters. Abstract: With the new generation of microwave instruments and, especially, the Ice Cloud Imager covering submillimeter frequencies, it is necessary to evaluate the performance of the operational Radiative Transfer model for TOVS (RTTOV). Thus, an intercomparison study has been conducted between RTTOV and the reference model ARTS (Atmospheric Radiative Transfer Simulator), with an emphasis on cloudy and precipitating conditions, covering frequencies between ≈ 53.6 and ≈ 664.0 GHz. Overall a rather good agreement is found between the δ -Eddington solution embedded in the scattering solver of RTTOV, RTTOV-SCATT, and the discrete ordinate solution embedded in ARTS. Under clear-sky conditions, given a consistent spectroscopy, the agreement is within 0.4 K over all frequencies considered. When idealized, homogeneous cloudy conditions are employed, the agreement is mostly ± 2 K; this range is exceeded only at high scattering conditions. However, the following weaknesses are identified: the δ -Eddington solution fails to produce deep enough brightness temperature depressions at increasingly high scattering conditions and is not sufficient to capture the phase function structures at size parameters above 2–3; conditions typically found at around 664.0 GHz. When realistic hydrometeor profiles are employed, δ -Eddington leads to a root mean squared error of 1 K, with individual errors between 0 and 4 K. Infrequently, and in localized areas, larger discrepancies are identified, exceeding 10 K. However, these inaccuracies stemming from the simplified physics of RTTOV-SCATT were found at least an order of magnitude smaller than the cloud and precipitation representation errors assigned in data assimilation. Thus, we support the use of RTTOV-SCATT at submillimeter frequencies for operational purposes.